A TYPOLOGICAL INVESTIGATION OF THE Y.B. MANGUNWIJAYA’S URBAN CHURCH - Rudy Trisno; Fermanto Lianto; Denny Husin (DIMENSI (Journal of Architecture and Built Environment), 2020)
As the iconic buildings in Yogyakarta, the Mangunwijaya’s churches contribute a great influence on the city. His wisdom is not only written in his books, but also has been implemented through his architectural projects, revealing a specific composition of a spiritual language. A qualitative study is used to reveal Mangunwijaya’s architectural principles, by using the tracing method to highlight the structural elements of his urban churches. A typological investigation is accompanied by retracing Mangunwijaya’s drawing, where its spatial composition and form are emphasized through points and lines. Hence, by eliminating decorative elements, the most fundamental components of the churches can be raised, consisting: 1) The roof as the most dominant element, a volume that suggests the openness of the building; 2) Landscape defines a mutual symbiosis between indoor and outdoor, stimulating communication and gesture; 3) A typological composition that respects a Roman-Catholic church’s principles while revealing a local identity.